Penerapan Pendekatan Matematika Realistik (PMR) untuk Meningkatkan Kemampuan Penjumlahan dan Pengurangan Dua Angka Siswa Kelas I SDN Cikupa - Andriani, Aas; Isrokatun, Isrokatun; Maulana, Maulana (Jurnal Pena Ilmiah, 2021)
Abstract This study aims to improve the ability to add and subtract two numbers by using a realistic mathematical approach. The research method used is pre-experimental research with one group pretest posttest design. So in the research process using one class as an experimental class. Instruments used in this research are to test numeracy, students' daily journal, interview guides and teacher observation sheet. The technique used to analyze the data in this study is quantitatively by processing the activity data of students, teachers, and also the results of the tests. Qualitative data processing is used to complete the results of the quantitative data. Based on the results of the data that has been obtained after carrying out the research, it can be seen that there is an increase in students' ability to add and subtract two-digit numbers by learning using a realistic mathematical approach. So it can be concluded that the application of a realistic mathematical approach is able to improve the ability to add and subtract two numbers in grade I students at SDN Cikupa. Â